A Conceptual Framework for Digital Competence of Students With Low Vision and Blindness. (January 2023) - Kamei-Hannan, Cheryl; Tuttle, Michael J.; Songkhao, Rujira
Introduction: Proficient use of technology requires many intersecting skills including literacy, citizenship, advocacy, self-determination, and digital competence. In this study, the authors engaged experts in the field of visual impairment in focus groups with the purpose of defining digital competence, discussing issues related to visual impairment, identifying specific skills, and organizing technology competencies.Methods: Purposeful sampling was used to recruit 32 assistive technology and literacy experts in the field of visual impairment to participate in a series of focus groups. Each focus group was presented with four main topics (1) defining digital competence, (2) identifying specific considerations for individuals with visual impairments (i.e., those who are blind or have low vision), (3) forming a list of technology competencies, and (4) categorizing competencies into an organized structure. Within-group consensus and across-group data saturation were achieved after nine focus groups were conducted via teleconferencing.Results: Focus groups led to three significant findings. First, the consensus was reached by participants on the definition of digital competence. Second, participants agreed upon considerations for individuals with visual impairments. Third, a set of 41 competencies was created. A consensus was not reached on categorizing the competencies. However, several themes arose including the need to address problem solving, accessibility, self-advocacy, citizenship, and self-determination, in addition to technology skills.Discussion: Authors concluded the study by presenting a framework for digital competence that may be used to guide future research.Implications for Practitioners: Students' success in digital learning environments is predicated on skills that extend beyond device usage. In addition to using digital tools efficiently and effectively, instruction should include opportunities for self-determination, access, problem solving, critical thinking, citizenship, and advocacy.